Cerebral infarction as initial manifestation of meningovascular neurosyphilis in an immunocompetent patient – A case report with long term follow‐up - Davor Batinić; Ronald Antulov; Inge Klupka‐Sarić; Anita Ivanković; Renata Jurina; Marijana Karlović Vidaković; Ivana Talić Drlje; Jurica Arapović (Clinical Case Reports, 2023)
Abstract To present a 29‐year‐old immunocompetent patient with neurosyphilitic changes characterized by multiple acute ischemic brain strokes along with significant narrowing of several large intracranial arteries. Ceftriaxone treatment for 14 days followed by benzathine benzylpenicillin weekly for additional 3 weeks, showed improvement in meningovascular changes.